Assessing the Welfare Cost of a Fixed Exchange-Rate Policy - Niels Arne Dam; Jesper Gregers Linaa (University of Copenhagen, Economic Policy Research Unit (EPRU), 2005)
This paper performs a welfare analysis based on the hypothetical scenario that Denmark gave up its peg and started conducting monetary policy according to a Taylor rule. For this we rely on a dynamic stochastic general equilibrium model for a small open economy that was estimated on Danish data using Bayesian methods. We obtain the result that the gain in welfare is equivalent to a permanent increase of around 0.8 pct in the level of consumption. Examining a range of alternative scenarios does not change this conclusion, unless we assume a degree of policy errors under the Taylor rule that is substantially larger than those estimated by other studies.
Keywords: E3; E4; E5; F4; 330; open economy; monetary policy; business cycles; welfare; Fester Wechselkurs; Wechselkurspolitik; Geldpolitik; Taylor-Regel; Allgemeines Gleichgewicht; Kleine offene Volkswirtschaft; Konjunktur; Dänemark